Influence Work Family Conflict and Burden Work to Turnover Intention on Amaris Hotel Teuku Umar - Rihayana, I Gede; Resa Adhika, I Nyoman; Putra Salain, Putu Pradiva (Akademi Komunitas MAPINDO, 2024)
The phenomenon that occurred at Harris Hotel Kuta regarding work family conflict and high workload, thereby increasing the turnover intention of workers due to the pressure of business competition in the industry hospitality. Workers, especially operational teams, have to do their work harder than usual because the number of staff must be minimized and the work per employee must be high to meet the company's expectations can achieve maximum work effectiveness. The aim of the research is to determine the effect of work family conflict on turnover intention and to determine the effect of workload on turnover intention at Harris Hotel Kuta Galleria Bali. Collection method data done with questionnaire. Sample in this study were 80 respondents. Determination of retrieval number of respondents was carried out with the sesnus method. The data analysis technique used is multiple linear regression, with software SPSS. Results test instrument show data valid And reliable. Results study showing that results work family conflict has a positive effect on turnover intention and workload results have a positive effect to turnover intention on Harris Hotel Kuta Gallery Bali. Keywords: work family conflicts, burden Work, turnover intention